UTILIZING ONLINE LEARNING TO ENHANCE ENGLISH SKILLS ON INTENSIVE ENGLISH CLASS - Tenny Murtiningsih (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2020)
The Covid-19 pandemic has transformed the learning system. The great impact on the learning system is that millions of schools and universities are now starting to practice online learning massively at all levels of education. Now, the online learning system is also used in Intensive English Class (IEC) at one university in Banjarmasin. Intensive English Class (IEC) is a one-year English program for the students. This study aimed to investigate the use of online learning to enhance English skills through Intensive English Class. This is a qualitative descriptive study. This study invited 339 freshmen students and six Intensive English Class instructors as respondents. The results of this study show that online learning at Intensive English Class could effectively improve students’ English skills. This can be seen from the data that 58.1% students agreed that the online learning could help them to enhance their English skills. It was also supported by their knowledge of how to use online learning well. This means that there is a good connection between utilizing online learning and the development of English skills on Intensive English Class.